2014
DOI: 10.1155/2014/756059
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Current Status and Strategies of Retinopathy of Prematurity Screening during 6 Years in Local Regions of China: Implication and Caution

Abstract: Purpose. To understand the current status of retinopathy of prematurity (ROP) screening in a province of North China. Methods. We retrospectively analyzed 5651 cases with ROP screening in the Provincial Screening Center of Hebei Province from January 2008 to December 2013. Results. 14.98% of all ROP patients and 1.56% of severe ROP patients required treatment. All the severe ROP patients met the criteria of screening. Severe ROP patients were detected at recommended initial screening time (4–6 weeks after birt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Within the 7 years of screening in our data, none of the infants who exceeded the UK screening criteria developed ROP, and we believe the yield of detecting treatable ROP in infants beyond the UK screening criteria is low, while taking into consideration cost-effectiveness in our public health system and avoiding unnecessary screening. Furthermore, a study from China found that only 0.26% of infants had severe ROP out of those infants who exceeded the UK screening criteria 22. Our study suggests that adopting the current international screening guidelines used in high-income countries is suitable and effective for our population, and incorporating a new criterion specific for our locality may not be necessary.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Within the 7 years of screening in our data, none of the infants who exceeded the UK screening criteria developed ROP, and we believe the yield of detecting treatable ROP in infants beyond the UK screening criteria is low, while taking into consideration cost-effectiveness in our public health system and avoiding unnecessary screening. Furthermore, a study from China found that only 0.26% of infants had severe ROP out of those infants who exceeded the UK screening criteria 22. Our study suggests that adopting the current international screening guidelines used in high-income countries is suitable and effective for our population, and incorporating a new criterion specific for our locality may not be necessary.…”
Section: Discussionmentioning
confidence: 69%
“…They suggest that a possible explanation for ROP in larger and more mature babies could be the lack of standardised high-quality neonatal care compared with high-income countries, and that very sick premature infants may have been too sick to travel for ROP screening in tertiary centres in China, which could have biased the data in favour of more mature infants. Thus, the Chinese screening criteria of up to 34 weeks GA or 2000 g birth weight is still recommended in China, although some centres recommend a narrower criteria of up to 32 weeks GA and/or birth weight up to 1800 g 22. Even though the babies in our locality are predominantly of the same Chinese ethnicity, the authors reported that there is still wide variation in the NICU practices in various parts of China (especially in monitoring oxygen supplementation and management of perinatal complications), as well as a wide variation in socioeconomic development, which we believe may explain the need for difference in screening criteria between Hong Kong and China.…”
Section: Discussionmentioning
confidence: 99%
“…Slightly different with US and UK criteria, the guidelines used in China include more mature infants, in order not to miss infants who may need treatment. Even so, in China, several reports on ROP screening included neonates with GA ranged from 32 weeks to 37 weeks or BW between 1500 g and 2000 g, and specified that more mature babies can develop severe ROP [ 6 , 7 , 13 , 26 ]. Chen et al [ 27 ] suggested in China infants with BW ≥ 2000 g should be examined at three weeks after birth.…”
Section: Discussionmentioning
confidence: 99%
“…Only 38.34% of patients were screened at 4-6 weeks postnatal. 10 Their study also highlighted the lack of understanding of ROP by parents and staff members, and the importance of raising awareness in staff members and parents about ROP.…”
Section: Discussionmentioning
confidence: 99%